2016
DOI: 10.1038/nrc.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in cancer

Abstract: The incidence of many cancer types is significantly higher in the male than female populations, with associated differences in survival. Occupational and/or behavioral factors are well known underlying determinants. However, cellular/molecular differences between the two sexes are also likely to be important. We are focusing here on the complex interplay that sexual hormones and sex chromosomes can have in intrinsic control of cancer initiating cell populations, tumor microenvironment and systemic determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
252
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(261 citation statements)
references
References 197 publications
(189 reference statements)
6
252
0
3
Order By: Relevance
“…In general, males have a higher incidence and mortality relative to females in cancers throughout the body, with the exception of a few cancers (e.g., gallbladder and anorectal cancers) (6)(7)(8). Similar patterns are present in intracranial tumors.…”
Section: Introductionsupporting
confidence: 49%
“…In general, males have a higher incidence and mortality relative to females in cancers throughout the body, with the exception of a few cancers (e.g., gallbladder and anorectal cancers) (6)(7)(8). Similar patterns are present in intracranial tumors.…”
Section: Introductionsupporting
confidence: 49%
“…Such studies suggested that sex hormones and sex chromosomes could intrinsically contribute to tumorigenesis [2], cancer genome instability [3], and tumor microenvironment ( Figure 1) [2,4]. However, despite these important observations, molecular signatures based on pan-omics profiles [5] across various cancer types have not yet been systematically explored in the post-genomics era.…”
mentioning
confidence: 94%
“…Previous studies focused on tumorigenesis and outcomes of treatments have highlighted sex-biased genetic and epigenetic features, and this was explained by the exclusive consideration of individual genes and single types of molecular data rather than employing a comprehensive system [2]. Such studies suggested that sex hormones and sex chromosomes could intrinsically contribute to tumorigenesis [2], cancer genome instability [3], and tumor microenvironment ( Figure 1) [2,4].…”
mentioning
confidence: 96%
See 2 more Smart Citations